Keepers of the Metaphorical Gate: The Role of Journal Editors - Edward Taylor; Tom Nesbit; David Boud; Miriam Zukas; Mike Osborne; Mary Alfred; Paulette Issac Savage; Bob Hill; Peter Jarvis (Adult Education Research Conference, 2007)
Academic journals are central to a discipline’s professionalism and are the principal means of communication. The purpose of this symposium is explore the nature academic journals, their purposes and what they reveal about the field from the perspective of nine editors whose primary mission is to cover the broad field of adult education.